Experimental tests and EDFM method to study gas injection in a fractured granite reservoir - Nie, Zhiquan; Xu, Feng; Ouyang, Jingqi; Li, Xiangling; Zhang, Juntao; Liu, Shiliang; Han, Jinqiang; Li, Da (Frontiers in Energy Research, 2023)
The development of granite reservoirs with high dip fractures has many difficulties, such as a high decline rate, early water breakthrough, and numerous economic losses. Gas injection is usually used to maintain the formation pressure to increase single well productivity, and could be carried out in fractured reservoirs to enhance oil recovery. When injecting associated gas, it meets the environmental protection requirements of the local government to further eliminate the flare, implementing the concept of green and low-carbon development. In this study, both laboratory tests and reservoir simulation have been done to study the feasibility and the benefit of associated gas injection in the research target. For physical stimulation, it mainly includes experiments such as associated gas injection expansion, slim tube, long core displacement, and relative permeability. Through these experiments, the changes in the recovery factor after depletion development and gas displacement are systematically described and the key controls are revealed for improving the recovery ratio of fractured basement reservoirs. For the simulation part, the embedded discrete fracture model processor combining commercial reservoir simulators is fully integrated into the research. A 3D model with complex natural fractures is built to perform the associated gas injection performance of the fractured granite reservoir. Complex dynamic behaviors of natural fractures can be captured, which can maintain the accuracy of DFNs and keep the efficiency offered by structured gridding. Depletion development and gas injection development strategy are optimized in this research. The result shows that oil recovery by using gas injection is increased by 16.8% compared with depletion development by natural energy.